The Electrical Conductivty Of Fe-Chitosan Schiff Base Complex - Boy Chandra Sitanggang; Zainal Abidin (Universitas Airlangga, 2020)
High electrical conductivity material Fe-Chitosan Schiff base produced via two stages mechanism, reaction of salicylaldehyde and chitosan in three necked flask following the formation of complex by soak Chitosan Schiff base in FeCl3 solution in various times. The formed Schiff base was confirmed by presence of imine at 1604.77 cm-1. Next, Fe absorption was analyzed by using ICP-MS gives highest results at 492,51 ppm at 5 hours immersion time. The electrical conductivity exhibit tendency to increase and the highest point at 3.5 x 10-6 S cm-1